Engineering of a DNA Polymerase for Direct m6A Sequencing. Issue 2 (7th December 2017) - Aschenbrenner, Joos; Werner, Stephan; Marchand, Virginie; Adam, Martina; Motorin, Yuri; Helm, Mark; Marx, Andreas
Abstract: Methods for the detection of RNA modifications are of fundamental importance for advancing epitranscriptomics. N 6 ‐methyladenosine (m 6 A) is the most abundant RNA modification in mammalian mRNA and is involved in the regulation of gene expression. Current detection techniques are laborious and rely on antibody‐based enrichment of m 6 A‐containing RNA prior to sequencing, since m 6 A modifications are generally "erased" during reverse transcription (RT). To overcome the drawbacks associated with indirect detection, we aimed to generate novel DNA polymerase variants for direct m 6 A sequencing. Therefore, we developed a screen to evolve an RT‐active KlenTaq DNA polymerase variant that sets a mark for N 6 ‐methylation. We identified a mutant that exhibits increased misincorporation opposite m 6 A compared to unmodified A. Application of the generated DNA polymerase in next‐generation sequencing allowed the identification of m 6 A sites directly from the sequencing data of untreated RNA samples. Abstract : Deliberate error : A KlenTaq DNA polymerase variant with elevated error rates opposite m 6 A but not unmodified A in an RNA template was evolved by using a primer‐extension‐based screening assay. The identified mutant was applied in a next‐generation sequencing (NGS) library preparation method and m 6 A sites could be directly identified in the sequencing data as mutational hotspots.